Pengaruh Media Pembelajaran Kincir Pintar Terhadap Kemampuan Keaksaraan Awal Anak Usia 5-6 Tahun di TK Santo Thomas 1 Medan - Hidayatul Munawwarah S; Niken Farida; Delfi Rosalina Duha (Departement of Mathematics Education, 2025)
This research aims to determine the effect of smart wheel learning media on the early literacy abilities of children aged 5 - 6 years at Santo Thomas 1 Medan Kindergarten. This type of research is quantitative research with a quasi-experimental research design. The sample selection technique used was random sampling. The sample in this study was all children aged 5 - 6 years at Kindergarten Santo Thomas 1 Medan, totaling 44 children who were combined into two groups, namely the experimental class and the control class. This research was analyzed using SPSS 22 with the normality test, homogeneity test, and hypothesis testing using the t test. Based on the results of research data analysis, it was found that the average value of the pretest and posttest, namely 10.61, increased to 16.17 and the results of the t test sample hypothesis test were sig (2-tailed) with pretest and posttest of 0.005 <0.05. The results of the t test analysis show that the value of t count > t table (2.955 > 1.68195) means that Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of the smart wheel learning media on the early literacy abilities of children aged 5 - 6 years at Santo Thomas 1 Medan Kindergarten